2005
DOI: 10.1111/j.1365-2427.2004.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic microhabitats and the distribution of macroinvertebrate assemblages in riffles

Abstract: 1. The influence of hydraulic conditions on the spatial distribution of macroinvertebrate assemblages was investigated in three riffles in a perennial Australian river. 2. Velocity, depth and variability of substrate roughness were measured at each of 56 macroinvertebrate sampling locations. Complex hydraulic variables (roughness Reynolds number, shear velocity, Froude number) were calculated from combinations of two or three of the directly measured variables. The biological significance of directly measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
146
1
14

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 47 publications
12
146
1
14
Order By: Relevance
“…In Achiras stream, the highest densities of drift were recorded in winter and spring, when the current velocity and precipitations exhibited the lowest values. Our results are consistent with those reported by other authors for Neotropical streams and rivers of medium order (Ramírez and Pringle 1998b;Corigliano et al, 1998). On the other hand, lower densities of drifting organisms were recorded during periods of and found that they are dissimilar.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In Achiras stream, the highest densities of drift were recorded in winter and spring, when the current velocity and precipitations exhibited the lowest values. Our results are consistent with those reported by other authors for Neotropical streams and rivers of medium order (Ramírez and Pringle 1998b;Corigliano et al, 1998). On the other hand, lower densities of drifting organisms were recorded during periods of and found that they are dissimilar.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of these taxa represents an important contribution because they increase the taxonomic richness and help to complement the baseline biodiversity information of a river system (Svendsen et al, 2004). The magnitude of drift responses to changes in flow depends on the time in which the last fluctuation occurred (Corigliano et al, 1998). In stable hydrological conditions over prolonged time periods, organisms have higher opportunities to associate with specific microhabitats and thus increase their densities (Poff and Ward, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Velocity was the most important variable to be related with the macroinvertebrate composition in both cases. This variable has already been demonstrated as one of the most important factors of macroinvertebrate community (Boyero and Bailey, 2001;Brooks et al, 2005;Guareschi et al, 2014). The importance of the CPOM resource for stream macroinvertebrate distribution has been previously stressed in similar Apennine ecosystems, particularly in relation to shredders distribution (Fenoglio et al, 2005).…”
Section: Discussionmentioning
confidence: 99%